Identification of Primary Facial Emotions in Relation to Level of Self-Criticism. (October 2019) - Strnádelová, Bronislava; Halamová, Júlia; Kanovský, Martin
The study analyzes the relationship between level of self-criticism and success in recognizing six primary emotions and neutral emotion in photographs from the Umeå University Database of Facial Expressions. The 134 participants were recruited from the general community using availability criteria. They completed the Forms of Self-Criticising/Attacking & Self-Reassuring Scale and a facial-emotion recognition task, writing down their identified emotion in open format. Bayesian multilevel model was used to model the probability of success on the facial-emotion recognition task. The results showed that a higher Inadequate Self score is a good positive predictor of success on the facial-emotion recognition task, while a higher Hated Self score is a good but negative predictor of success. Our results indicate that it is meaningful to distinguish between Hated Self and Inadequate Self on the Forms of Self-Criticising/Attacking & Self-Reassuring Scale. Moreover, this difference could be, if supported in future studies, used for diagnosing pathologically self-critical people or for planning treatment and interventions for highly self-critical people.